Pengembangan electronic module berbasis EPUB dengan model cooperative script pada hasil belajar siswa - Shofie Widya Salsabilla; I Nyoman Suputra (Universitas Negeri Malang, 2022)
Educators in the Internet of Things (IoT) era are expected to fully utilize advances in science and technology, as well as to integrate technology into the learning process. Electronic modules are educational learning resources that are currently available in digital format. To maximize the development of learning resources, it can be equipped with appropriate learning methods to improve learning outcomes and achieve learning objectives. The researcher's goal in conducting research and development is to create educational products in the form of electronic modules based on EPUB and to determine the effect of using electronic modules with cooperative learning models on student learning outcomes. The ADDIE development model is employed in this study. The results of the research development are in the form of an EPUB-based E-Module product which was developed with the help of Sigil software. For the product trial results, the average expert validation score is 94.2%, indicating that the e-module is suitable for use as a learning resource. The final post-test score obtained by students revealed a 6% difference, with the experimental class outperforming the control class. According to the findings of this study, an EPUB-based electronic module based on the cooperative script learning model is feasible and capable of increasing student scores. Pendidik di era Internet of Things (IoT) diharapkan dapat memanfaatkan sepenuhnya kemajuan ilmu pengetahuan dan teknologi, serta mengintegrasikan teknologi ke dalam proses pembelajaran. Modul elektronik merupakan sumber belajar pendidikan yang saat ini tersedia dalam format digital. Untuk memaksimalkan pengembangan sumber belajar, dapat dilengkapi dengan metode pembelajaran yang tepat untuk meningkatkan hasil belajar dan mencapai tujuan pembelajaran. Tujuan peneliti dalam melakukan penelitian dan pengembangan adalah untuk menciptakan produk pendidikan berupa modul elektronik berbasis EPUB dan untuk mengetahui pengaruh penggunaan modul elektronik dengan model pembelajaran kooperatif terhadap hasil belajar siswa. Model pengembangan ADDIE digunakan dalam penelitian ini. Hasil pengembangan penelitiaan berupa produk E-Modul berbasis EPUB yang dikembangkan dengan berbantuan software Sigil. Untuk hasil uji coba produk menghasilkan rata-rata skor validasi ahli adalah 94,2%, menunjukkan e-modul layak digunakan sebagai sumber belajar. Nilai akhir post-test yang diperoleh siswa menunjukkan perbedaan 6%, dengan kelas eksperimen mengungguli kelas kontrol. Berdasarkan temuan penelitian ini, modul elektronik berbasis EPUB berbasis model pembelajaran cooperative script layak dan mampu meningkatkan nilai siswa.